Understanding the collecting experience: purchase motivations and social collecting behaviors - Vergara, Raymond Allan G.; Santos , Joseph Emil (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This qualitative case study explores the purchase motivations and collecting behavior of self-assessed Funko Pop collectors. It finds that the individual collector's self-identification influences individual purchase and collection decisions. It also finds that social collecting behaviors may influence individual collecting behavior, suggesting that collecting communities may establish collecting norms and experiences. This study maps out the collecting experience, provides a unique perspective on social collecting behaviors, explores the nuances of the collecting experience, and recommends potential direction for managers.